Surface to volume ratio of carbon nanohorn - a crucial factor in co 2/ch4 mixture separation - Furmaniak, Sylwester; Terzyk, Artur; Kaneko, Katsumi; Gauden, Piotr; Kowalczyk, Piotr; Ohba, Tomonori (Elsevier BV, 2014)
Using the first realistic model of single walled carbon nanohorn and molecular simulation data we show the 3D graphs relating the selectivity of CO2/CH4 separation with a surface to volume ratio of a nanohorn, the total mixture pressure and the mole fraction of CO2 in the bulk phase. It is proved that surface to volume ratio is a crucial parameter determining the selectivity. Finally, the equation is proposed, making possible to predict the selectivity of a nanohorn for separation of CO2/CH4 mixture.